Inhibitability of Carbene and Silylene Complexes against Rhizoctonia solani and Magnaporthe oryzae: An in silico Study - Nguyen Thi Ai Nhung (Current Topics on Chemistry and Biochemistry Vol. 7, 2023)
Copper carbenes and silylenes are considered for the inhibitory effect of the considered complexes towards Rhizoctonia solani (PDB-4G9M) and Magnaporthe oryzae (PDB-6JBR) in rice. Quantum chemical calculations of copper carbene and silylene complexes (Cu-NHC1, Cu-NHC2, Cu-NHSi1, and Cu-NHSi2) were obtained using density functional theory (DFT). Their inhibitability towards the targeted proteins (4G9M; 6JBR) was evaluated using molecular docking analysis. Quantum chemical analysis predicts the stability of the studied complexes. Their electronic configurations are justified and highly conducive to intermolecular interaction. Regarding the carbenes/silylenes-4G9M structures, the stability is estimated in the order [Cu-NHC2]-4G9M (DS -12.9 kcal.mol-1) > [Cu-NHSi1]-4G9M (DS -11.8 kcal.mol-1) = [Cu-NHSi2]-4G9M (DS -11.7 kcal.mol-1) > [Cu-NHC1]-4G9M (DS -11.4 kcal.mol-1); while the order for the carbenes/silylenes-6JBR adducts is [Cu-NHSi2]-6JBR (DS -13.4 kcal.mol-1) > [Cu-NHC2]-6JBR (DS -13.0 kcal.mol-1) = [Cu-NHSi1]-6JBR (DS -12.6 kcal.mol-1) > [Cu-NHC1]-6JBR (DS -12.3 kcal.mol-1). The findings of this study reveal that copper-carbenes and copper-silylenes have the potential to protect against the infection of fungi Rhizoctonia solani and Magnaporthe oryzae, which encourages further research.